Changing Village-Typology of Rural Settlements in Hungary at the Beginning of the Third Millennium - Beluszky, Pál; Sikos, T. Tamás (Discussion Papers, 2012)
With the change of regime in Hungary (1989-1990) not only the autocratic, state-capitalist “socialist” regime was replaced by the political system of democ¬ratic market economy but also fundamental changes have undergone in the proc¬esses formulating rural settlements. The rate of agricultural population kept de¬creasing, the majority of agricultural factories fell apart or was reorganized, so that private farming could gain ground. These processes alongside with the changes in the availability of basic supply and in the structure of the labour market reformu¬lated the image of rural settlements, the society and the geographic features they possessed in the socialist era. This study aims to surveying this process by estab¬lishing the typology of rural settlements at the beginning of the 21st century by the method of factor- and cluster analysis.